The Effect of Propofol on Onset and Sedation in Diabetic Mellitus Rat (Rattus norvegicus) - Erwin Erwin; Rusli Rusli; Zuraidawati Zuraidawati; Fadillah Irwansyah (Universitas Syiah Kuala, 2014)
This research aimed to examine the time of onset and sedation on diabetic mellitus (DM) rat (Rattus norvegicus) by propofol. This study used 8 female wistar rats 2-3 months old and 150-200 grams of bodyweight, fed with standard feed and water ad libitum. Samples were divided into two groups. Group 1 (KI) as a control group was injected intraperitoneally with aloxan solvent and group 2 (KII) was injected intraperitoneally with 150 mg/kg bodyweight aloxan. Blood glucose was checked 10 days after aloxan injection, DM was categorized if the blood glucose over 150 mg/dl. All rats were injected intravenously with propofol 1% with the dose of 10 mg/kg bodyweight. Onset and sedation time was counted using stopwatch after propofol injection. The result showed that mean (±SD) of onset on KI and KII were 1.39±0.49 and 8.64±1.23 seconds, consecutively and they were significantly different at P0.01. Whilst mean (±SD) of sedation KI and KII were 12.12±1.47 minutes and 7.62±1.61 minutes, respectively. The onset and sedation time of KI was significantly different from KII P0.01. The conclusion of this research was DM affects time of onset and sedation when wistar strain rats were anesthetized by 1% propofol.Key words: rats, diabetic mellitus, propofol, onset, sedation